Decision Support System for Selection of the Best Students in SDIT Gema Nurani - Sembel, Farah Ulfa; Ziveria, Mira (I-STATEMENT, 2018)
Sekolah Dasar Islam Terpadu (SDIT) Gema Nurani is one of the schools that stands on an Indonesian Foundation. SDIT Gema Nurani is located in Bekasi. SDIT Gema Nurani has several programs, one of the best is student selection program. The system in the selection of the best students still use a conventional system in the form of manual recording in a Microsoft Excel document that resulted in the work in the record into a long time that required a computer-based applications. In doing these calculations the student section will take a long time and often the error of calculating the value. This study aims to build a decision support system application the best student selection using Simple Additive Weighting (SAW) method. System development method in building application usingprototype model, stage in building system that is by using requirement and design analysis using Unified Modeling Language (UML) and implemented with Hypertext pre protocol program (PHP). The result of the research is a web-based application that can perform the calculation of values to determine the best students with the categories and criteria provided and accessible to wali kelas and students as needed.